Dismilaritas Kadar Low Density Lipoprotein Kolesterol pada Pasien Dislipidemia dengan Metode Homogenous Formula Friedewald di RSUD Mardi Waluyo Kota Blitar: Dissimilarity of Low Density Lipoprotein Cholesterol Levels in Dyslipidemia Patients Using the Friedewald Homogenous Formula Method at Mardi Waluyo Regional Hospital, Blitar City - Hartati Tuna; MM Riyaniarti Estri Wuryandari; Mely Purnadianti; Nita Damayanti; Vivien Dwi Purnamasari; Gerardin Ranind Kirana (Universitas Negeri Semarang, 2025)
Dyslipidemia is one of the primary risk factors for vascular disease, which can lead to an increase in the number of lipid profile tests. Low-density lipoprotein cholesterol (LDL-C) is one of the signs of dyslipidemia and can be examined using the direct method (homogeneous) or the Friedewald formula. This examination method has its own advantages and disadvantages. This study aims to determine the difference in LDL cholesterol levels using the direct method and the Friedewald formula in dyslipidemia sufferers at Mardi Waluyo Hospital, Blitar City. The research design carried out is a cumulative analytical research with a cross survey approach. This study was conducted on 40 patients who underwent lipid profile examinations at the Laboratory of Mardi Waluyo Hospital, Blitar City. Blood samples that are examined and included in the dyslipidemia criteria are then checked for LDL cholesterol levels with the Friedewald formula. Based on the results of the study, the results ofthe statistical analysis of the Independent test sample t-test with a meaningfulness level of 95% (α = 0.05) were obtained by the LDL t statistic result (1.706) < t table 2.02439. There was no significant difference in the results of the LDL cholesterol examination of the direct method and Friedewald formula in people with dyslipidemia, For this reason, further research is needed to determine LDL cholesterol levels, both in the extract and with the Friedewald formula, using the gold standard method for LDL cholesterol examination in accordance with the recommendations of the National Cholesterol Education Program (NCEP) is ultracentrifugation as a comparison of LDL cholesterol research